The critical role of uterine CD31 as a post-progesterone signal in early pregnancy. Issue 5 (November 2017) - Lee, Seo-Ho; Kim, Byung-Ju; Kim, Uh-Hyun
Abstract : CD31 has been shown to play a role in endothelial cell migration and angiogenesis, which are critical to the formation and function of the endometrium and myometrium in uterine development during early pregnancy. However, the role of CD31 in uterine receptivity during blastocyst implantation is poorly understood. The pregnancy rate in CD31 −/− female mice mated with CD31 +/+ male mice was higher than that observed in CD31 +/+ female mice mated with CD31 +/+ male mice. During the receptive phase of implantation, uterine glands were more developed in CD31 −/− mice than in CD31 +/+ mice, and the uterine weights of CD31 −/− mice were increased. Leukemia inhibitory factor (LIF) was highly expressed in the CD31 −/− mice during implantation and the expression of LIF was up-regulated by estradiol-17β ( E 2 ) + progesterone ( P 4 ) in ovariectomized CD31 −/− mice, compared with CD31 +/+ mice at 8 h after hormone treatment. E 2 -induced protein synthesis was inhibited by P 4 in the CD31 +/+ uterus, but not in the uterus of CD31 −/− mice. Also, STAT3, HAND2, LIF, and mTOR signals were enhanced in CD31 −/− mice. Stromal DNA replication was highly activated in the uterus of CD31 −/− mice, manifested by upregulated cyclin series signaling and PCNA expression after E 2  +  P 4 treatment. Collectively, CD31 inhibits E 2 -mediated epithelial proliferation via recruitment and phosphorylation of SHP-2 upon receiving P 4 signal in early pregnancy.